Why Employers Use Flexible Staffing Arrangements: Evidence from an Establishment Survey - Susan N. Houseman (W.E. Upjohn Institute for Employment Research, 2000)
This paper examines which employers use flexible staffing arrangements, why they use these arrangements, and their implications for workers and public policy, drawing on a nationally representative survey of private sector establishments. Use of flexible staffing arrangements – including temporary help agency, short-term, on-call, regular part-time, and contract workers – is widespread and two-thirds of employers believe this use will increase in the near future. Traditional reasons concerning the need to accommodate fluctuations in workload or absences in staff are the most commonly cited reasons for using all types of flexible staffing arrangements. Many employers also use agency temporaries and part- time workers to screen candidates for regular positions. Finally, savings on benefits costs is an important factor determining employers' use of flexible staffing arrangements. Workers in flexible staffing arrangements typically are not covered by regulations governing benefits, and they typically do not receive key benefits, like pension benefits and health insurance, when these benefits are offered to regular full-time workers.
Additional information: A revised version of this paper appears in Industrial and Labor Relations Review, Vol. 55, No. 1 (October 2001), pp. 149-170. Please cite the revised version.
Keywords: J4; I3; 330; flexible staffing; contingent work; part-time work; Houseman